Photo-curing silicon-based ceramic core slurry for investment casting and preparation method and application of photo-curing silicon-based ceramic core slurry
Through the specific group distribution ratio and process processing of photocured silicon-based ceramic core slurry, the problem that traditional ceramic core manufacturing technology is difficult to meet the complex structure and high precision requirements is solved, and high strength, high precision and low sintering shrinkage is achieved. Preparation of silicon-based ceramic cores.
Patent Information
- Application Number
- CN202411500614.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Traditional ceramic core manufacturing technology is difficult to meet the needs of complex structures and high precision, and the process is complex and the cost is high.
A photocured silicon-based ceramic core slurry is used to prepare a silicon-based ceramic core with high strength, high precision and low sintering shrinkage through specific group distribution ratios and process processing.
The preparation of silicon-based ceramic cores with high strength, high precision and low sintering shrinkage is achieved, and is suitable for ceramic core manufacturing with complex structures and high precision requirements.
Smart Images

Figure CN119387496A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of precision casting, and particularly relates to a light-cured silicon-based ceramic core slurry for investment casting, a preparation method and application thereof. Background Art
[0002] With the advancement of aviation technology, higher standards have been put forward for the temperature resistance of aircraft engine turbine blades. Ceramic cores are key transition parts in the manufacture of turbine blades. Based on the basic principles of fluid mechanics and heat transfer mechanics, the structure of the hollow blade cavity has become more complex, and more stringent requirements have been put forward for the performance of ceramic cores. Traditional ceramic cores mainly use hot injection technology, which is suitable for the mass production of ceramic cores with simple structures. Due to the limitations of molds, it is relatively expensive, time-consuming, and has low molding accuracy. It is also difficult to prepare ceramic cores with complex structures. The traditional process of preparing highly complex double-walled silicon-based cores and precision silicon-based inner cavities requires multiple sets of molds, which is complicated and costly.
[0003] The photo-curing 3D printing technology has no mold constraints in the molding process, and the error range of the printing model design and modification is large. It is one of the important methods for developing ceramic cores with complex structures. How to prepare silicon-based ceramic core casting slurry with high solid content, high molding accuracy, high printing performance, high reaction efficiency, and more stable and excellent flow and sedimentation performance for additive manufacturing has become one of the problems that this technology urgently needs to solve, and it is also a key technology to ensure the size of the overall hollow engine blade. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a photocurable silicon-based ceramic core slurry for investment casting and a method for preparing the same. The slurry has stable flow and sedimentation performance and can be used for additive manufacturing of photocurable integrated high-strength (room temperature bending strength ≥15MPa, 1500 high temperature strength ≥20MPa), high-precision (molding error ≤20μm), and low sintering shrinkage (<2.5%) silicon-based ceramic cores, which is of great significance for the mass production of complex ceramic cores for investment casting industry.
[0005] In a first aspect, the present invention provides a photocurable silicon-based ceramic core slurry for investment casting, which comprises the following components based on 100 parts by total weight of the silicon-based ceramic core slurry: 70 to 85 parts of ceramic powder, 10 to 25 parts of photosensitive resin, 2 to 5 parts of photoinitiator, 1 to 5 parts of dispersant, 0.2 to 1.2 parts of anti-settling agent and 0.01 to 0.2 parts of light absorber; the ceramic powder is composed of fused quartz powder, alumina ceramic powder and zirconium silicate ceramic powder in a weight ratio of 50 to 90:5 to 15:2 to 10; the particle size of the fused quartz powder is 2 to 30 μm, and the purity is ≥95wt%; the particle size of the alumina ceramic powder is 20 to 40 μm, and the purity is ≥95wt%; the particle size of the zirconium silicate ceramic powder is 20 to 50 μm, and the purity is ≥95wt%.
[0006] The particle size and purity of each powder raw material are important. When they are within the scope of the present invention, it is easy to prepare a photocured silicon-based ceramic core with higher strength.
[0007] In some embodiments, the light absorber is a mixed azo compound, preferably a mixture of 2,2'-(3,3'-dichloro-1,1'-biphenyl-4,4'-disazo)bis[N-(2,4-dimethylphenyl)-3-oxo-butyramide], N,N-dimethyl-4-(phenylazo)aniline and 2,2'-[(3,3'-dichloro[1,1'-biphenyl]4,4'-diyl)bis(azo)]bis[N-(2-methylphenyl)]-3-oxobutyramide.
[0008] The structural formula of 2,2'-(3,3'-dichloro-1,1'-biphenyl-4,4'-diazo)bis[N-(2,4-dimethylphenyl)-3-oxo-butyramide] is as follows:
[0009]
[0010] The structural formula of 2,2'-[(3,3'-dichloro[1,1'-biphenyl]4,4"-diyl)bis(azo)]bis[N-(2-methylphenyl)]-3-oxobutanamide is as follows:
[0011]
[0012] The structural formula of N,N-dimethyl-4-(phenylazo)aniline is as follows:
[0013]
[0014] The multiple mixed light absorbers used in the present invention can better ensure the accuracy of the ceramic slurry during the light curing molding process. Specifically, the azo compounds contain a large number of conjugated unsaturated bonds, and the azobenzene functional group can induce trans-to-cis photoisomerization under the irradiation of ultraviolet light, so that the specific azobenzene functional group can absorb ultraviolet rays of different wavelengths. The three azo compounds used in the present invention (2,,2'-(3,3'-dichloro-1,1'-biphenyl-4,4'-diazo)bis[N-(2,4-dimethylphenyl)-3-oxo-butyramide], N,N-dimethyl-4-(phenylazo)aniline and 2,2'-[(3,3'-dichloro[1,1'-biphenyl]4,4'-diyl)bis(azo)]bis[N-(2-methylphenyl)]-3-oxobutyramide) can absorb ultraviolet light in the range of 350 to 450 nm, including the wavelength of ultraviolet light for photocuring 3D printing (365 to 405 nm), and the three selected azo compounds can also be fully dissolved in the photosensitive resin defined in the present invention, and a reasonable ratio can effectively increase the printing accuracy and greatly improve the size quality of the molding core.
[0015] In some embodiments, the mass ratio of 2'-(3,3'-dichloro-1,1'-biphenyl-4,4'-diazo)bis[N-(2,4-dimethylphenyl)-3-oxo-butyramide], N,N-dimethyl-4-(phenylazo)aniline and 2,2'-[(3,3'-dichloro[1,1'-biphenyl]4,4'-diyl)bis(azo)]bis[N-(2-methylphenyl)]-3-oxobutyramide is 2-6:1-3:1-2.
[0016] In some embodiments, the photosensitive resin is a mixture of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and bisphenol A epoxy acrylate.
[0017] The photosensitive resin of the invention is composed of three bifunctional active diluents, namely, 1,6-hexanediol diacrylate, bisphenol A epoxy acrylate and tripropylene glycol diacrylate, and one trifunctional active diluent, namely, trimethylolpropane triacrylate. The bifunctional active diluent has a large volume shrinkage during curing due to its small molecular weight during the photocuring process. Adding a proper amount of the trifunctional active diluent can effectively reduce the volume shrinkage during curing and reduce the molding defects of the ceramic core.
[0018] In some embodiments, the mass ratio of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate and bisphenol A epoxy acrylate is 5-10:1-4:1-3:1-2.
[0019] In some embodiments, the photoinitiator is a mixture of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate.
[0020] The ultraviolet absorption wavelength of 2-hydroxy-2-methyl-1-phenyl-1-propanone is 260-370 nm, the ultraviolet absorption wavelength of 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone is 330-385 nm, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate has absorption peaks at 350-380 nm and 422 nm. Therefore, the use of a mixed photoinitiator can adapt to 3D printing equipment with different wavelengths, thereby expanding the application scope of the present invention.
[0021] In some embodiments, in the photoinitiator, the mass ratio of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate is 1-2:1-5:3-5.
[0022] In some embodiments, the dispersant is selected from at least three of polyphosphate solution, modified polyurethane solution, phosphate ester, propylene glycol methyl ether acetate, butyl acetate and alkylbenzene; and / or, the anti-settling agent is selected from at least three of polyhydroxycarboxylic acid amide solution, modified urea solution, xylene, isobutanol, N-methylpyrrolidone.
[0023] The mixed dispersant used in the present invention can better ensure that the silicon-based ceramic powder is more evenly distributed in the photosensitive resin and has better fluidity. The mixed anti-settling agent can provide further support for the dispersant, and the two have a synergistic effect, which can better ensure the service life of the silicon-based ceramic core slurry and ensure the stability of the molding batch.
[0024] In some embodiments, the dispersant is composed of polyphosphate solution, phosphate and alkylbenzene in a mass ratio of 1-2:1-3:1-4.
[0025] In some embodiments, the anti-settling agent is composed of modified urea solution and xylene in a mass ratio of 1-2:1-4.
[0026] In a second aspect, the present invention provides a method for preparing the aforementioned light-cured silicon-based ceramic core slurry for investment casting, comprising: mixing and ball-milling the raw materials, and then vacuum degassing.
[0027] In some embodiments, the preparation method of the aforementioned photocurable silicon-based ceramic core slurry for investment casting includes: 1) placing fused quartz powder, alumina ceramic powder, zirconium silicate ceramic powder and a certain proportion of deionized water into a ball mill, followed by vacuum ball milling; 2) sieving the ball-milled mixture and drying it to obtain a silicon-based ceramic core powder that is evenly mixed after drying; 3) mixing the remaining raw materials in proportion to obtain a photosensitive resin premix; 4) adding the silicon-based ceramic core powder of step 2) to the photosensitive resin premix of step 3) and ball milling for 6 hours; 5) taking out the ball-milled ceramic slurry and subjecting it to vacuum degassing to obtain the result.
[0028] In a third aspect, the present invention provides the use of the aforementioned light-cured silicon-based ceramic core slurry for investment casting in the preparation of complex silicon-based ceramic cores.
[0029] In a fourth aspect, the present invention provides a method for preparing a silicon-based ceramic core, comprising the steps of printing a blank using a ceramic 3D printing device, and further degreasing and sintering the blank to obtain a finished silicon-based ceramic core: wherein the step of printing the blank comprises:
[0030] a. Set the slice thickness to 10-40 microns, set the printing parameters to 10-30 seconds, 20-35 mW / cm 2 , using the first silicon-based ceramic core slurry for printing; based on the total weight of the first silicon-based ceramic core slurry as 100 parts, it includes the following components: 70-85 parts of ceramic powder, 10-25 parts of photosensitive resin, 2-5 parts of photoinitiator, 1-5 parts of dispersant, 0.2-1.2 parts of anti-settling agent and 0.15-0.2 parts of light absorber.
[0031] b. Set the slice thickness to 40-80 microns, set the printing parameters to 5-25s, 25-35mW / cm 2 , using a second silicon-based ceramic core slurry for printing; based on the total weight of the second silicon-based ceramic core slurry as 100 parts, it includes the following components: 70-85 parts of ceramic powder, 10-25 parts of photosensitive resin, 2-5 parts of photoinitiator, 1-5 parts of dispersant, 0.2-1.2 parts of anti-settling agent and 0.1-0.15 parts of light absorber.
[0032] c. Set the slice thickness to 80-120 microns, set the printing parameters to 5-20 seconds, 25-35 mW / cm 2 , using a third silicon-based ceramic core slurry for printing; based on the total weight of the third silicon-based ceramic core slurry as 100 parts, it includes the following components: 70-85 parts of ceramic powder, 10-25 parts of photosensitive resin, 2-5 parts of photoinitiator, 1-5 parts of dispersant, 0.2-1.2 parts of anti-settling agent and 0.05-0.1 parts of light absorber.
[0033] d. Set the slice thickness to 120-200 microns, set the printing parameters to 5-15s, 15-35mW / cm 2 , using the fourth silicon-based ceramic core slurry for printing; based on the total weight of the fourth silicon-based ceramic core slurry as 100 parts, it includes the following components: 70-85 parts of ceramic powder, 10-25 parts of photosensitive resin, 2-5 parts of photoinitiator, 1-5 parts of dispersant, 0.2-1.2 parts of anti-settling agent and 0.01-0.05 parts of light absorber.
[0034] In combination with the slurry prepared in the above steps, the present invention also optimizes the exposure parameters and the light absorber content in the slurry to obtain the above optimal printing method. Specifically, the coupling relationship between the light absorber content, exposure parameters and molding parameters is solved by using a method combining numbers and shapes. Figure 2 , and obtain the light absorber content and exposure parameters with the highest accuracy under different molding parameters.
[0035] Decoupling calculation formula and description
[0036]
[0037] Formula (1) represents the relationship between the cured thickness and the exposure energy, where: C d is the cured thickness; E d0 is the incident energy dose, E d is the minimum UV energy that can initiate photopolymerization, S d Sensitivity in the depth direction, A d is the attenuation factor of depth.
[0038]
[0039] Formula (2) is A in Formula 1 d The detailed expression of φ is: p and ε d are the molar extinction coefficients of the photoinitiator and light absorber in the ceramic slurry, η p and η d represent the molar concentrations of the photoinitiator and light absorber in the ceramic slurry, respectively. sc It represents the scattering length of the entire slurry when particles scatter.
[0040]
[0041] Formula (3) represents the relationship between curing accuracy and exposure energy, where: Sw is the curing sensitivity in the width direction, A w is the width attenuation factor, which also satisfies S w =1 / A w , E w0 It is also expressed as incident energy. Combining Eq.2, under the same exposure conditions, it can be considered that E w0 =E d0 , E w It is the apparent critical energy at which over-curing occurs in the width direction.
[0042] C d =S t ×1.1(~1.35)×100%#(4)
[0043] Formula (4) represents the relationship between slice thickness and solidification thickness, where:
[0044] C d is the cured thickness; S t is the slice thickness.
[0045] Through the above four formulas, it is not difficult to find that the curing thickness and curing accuracy are determined by the size of the ultraviolet light, and the slice thickness is determined by the printing process. Therefore, there is a coupled relationship between the slice thickness, the amount of light absorber added, and the exposure parameters.
[0046]
[0047] Formulas (5) to (7) respectively represent the relationship of integration and decoupling of Formulas 1, 3, and 4. Figure 1 is the solution obtained according to formula (7), S0~S4 represent the content of additives, the step length is 0.025wt.%, the amount of S0 added is 0, and the amount of S4 added is 0.1wt.%. Where a represents the local enlarged view of the curve when the slice thickness is 110~135 microns. Through the analysis of this curve, it can be obtained that the closer to the red line, the higher the curing accuracy and the higher the accuracy of the printed ceramic core. Since no light absorber is added to the S0 curve, its slope is too large, indicating that fine structures cannot be printed. K wd The ratio of equation 1 and equation 3 corresponds to Figure 1 For example, when the curing thickness is 100μm, the curing thickness calculated by formula 4 should be 110~135μm. Figure 1 The horizontal red area of 110-135 μm is drawn as the optimal curing range. When the curve is close to the red dotted line, it means that the addition amount is optimal. At the same time, the intersection of the red dotted line and the blue line can be determined by combining formula 1 and Figure 2 The exposure parameters at this time can be inferred in reverse, and the light absorber content in formula (7) can be determined.
[0048] Figure 2 is the relationship between the amount of light absorber added and the curing depth, Figure 3 This is the relationship between the amount of light absorber added and the curing accuracy. Figure 4 These are the test results of the effects of different amounts of light absorbers on the accuracy of the test piece.
[0049] The printing method of the silicon-based ceramic core provided by the present invention further improves the precision of the finished product by accurately controlling the content of the light absorber in the slurry and the printing parameters, and provides technical support for more stable and industrialized preparation of silicon-based ceramic cores.
[0050] The beneficial effects of the present invention are:
[0051] The present invention uses a powder obtained by compounding fused quartz powder of specific particle size and purity, alumina ceramic powder and zirconium silicate ceramic powder as the ceramic powder of the silicon-based ceramic core slurry, which greatly improves the mechanical properties of the silicon-based ceramic core (room temperature bending strength ≥ 15MPa, 1500℃ high temperature strength ≥ 20MPa). The ceramic powder is precisely controlled in weight ratio with photosensitive resin, photoinitiator, dispersant, anti-settling agent and light absorber, and with the help of suitable 3D printing parameter settings, a silicon-based ceramic core with high strength and high precision can be prepared to meet actual use requirements.
[0052] The slurry provided by the present invention has a solid content of >70 vol% and a slurry viscosity of <10 Pa·s. After standing for 7 days, no obvious sedimentation occurs. The slurry has the characteristics of high solid content, good fluidity and good stability. At the same time, the higher solid content also significantly reduces the sintering shrinkage of the prepared light-cured silicon-based ceramic core, thereby improving the dimensional accuracy of the molded silicon-based ceramic core. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is the solution obtained by decoupling the number and shape;
[0054] Figure 2 is the relationship between the amount of light absorber added and the curing depth, where: a is the effect of the amount of light absorber added on the curing depth behavior of the slurry; b is the value of Sd calculated using formula 1 in a, and the fitting graph using formula 2 and formula 6;
[0055] Figure 3 is the relationship between the amount of light absorber added and the curing accuracy, where: a is the effect of the amount of light absorber added on the curing accuracy behavior of the slurry; b is the value of Sd calculated using formula 1 in a, and the fitting graph using formula 2 and formula 6;
[0056] Figure 4The test results of the influence of different contents of light absorbers on the accuracy of the test piece are shown in the upper right corner. The model diagram of the cube is shown. The tighter the fit, the better the molding stability. The 1.1mm between the holes in the lattice structure indicates the higher the molding accuracy. Among them: a is the model designed to verify the accuracy; b is the accuracy test diagram when the light absorber addition amount is 0; c is the accuracy test diagram when the light absorber addition amount is 0.025wt.%; d is the accuracy test diagram when the light absorber addition amount is 0.05wt.%; e is the accuracy test diagram when the light absorber addition amount is 0.1wt.%;
[0057] Figure 5 This is a picture of the high-precision silicon-based ceramic core sample prepared in Example 3. DETAILED DESCRIPTION
[0058] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] In the following examples, the dispersant is a polyphosphate solution, a phosphate and an alkylbenzene in a mass ratio of 1.5:2:3, the anti-settling agent is a modified urea solution and xylene in a mass ratio of 1.5:2, and the light absorber is 2'-(3,3'-dichloro-1,1'-biphenyl-4,4'-diazo)bis[N-(2,4-dimethylphenyl)-3-oxo-butyramide], N,N-dimethyl-4-(phenylazo)aniline and 2,2'-[(3,3'-dichloro[1,1'-biphenyl]4,4'-diyl)bis(azo)]bis[N-(2-methylphenyl)]-3-oxobutyramide in a mass ratio of 3:2:1.
[0060] Example 1
[0061] This embodiment provides a light-cured silicon-based ceramic core slurry for investment casting, and the preparation method is as follows:
[0062] 1) placing fused quartz powder, alumina ceramic powder and zirconium silicate ceramic powder and a certain proportion of deionized water into a ball mill, followed by vacuum ball milling;
[0063] 2) sieving the ball-milled mixture and drying it to obtain a uniformly mixed silicon-based ceramic core powder;
[0064] 3) mixing 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), trimethylolpropane triacrylate (TMPTA), a photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), a dispersant, an anti-settling agent and a light absorber to obtain a photosensitive resin premix;
[0065] 4) adding the silicon-based ceramic core powder from step 2) into the photosensitive resin premix from step 3) and ball milling for 6 hours;
[0066] 5) The ball-milled ceramic slurry is taken out and subjected to vacuum degassing treatment to obtain a photocurable silicon-based ceramic core slurry for investment casting that can be printed.
[0067] The amount of each component added to the slurry is as follows:
[0068]
[0069]
[0070] The slurry obtained in Example 1 was subjected to a sedimentation experiment and a viscosity test. The results showed that the slurry did not show obvious sedimentation after standing for 7 days, indicating that the slurry had good stability. -1 The viscosity is 9.9 Pa·s, which has good fluidity.
[0071] Example 2
[0072] This embodiment provides a light-cured silicon-based ceramic core slurry for investment casting. The preparation method is the same as that of Example 1. The amounts of each component added to the slurry are as follows:
[0073]
[0074] The slurry obtained in Example 2 was subjected to a sedimentation experiment and a viscosity test. The results showed that the slurry did not show obvious sedimentation after standing for 7 days, indicating that the slurry had good stability. -1 The viscosity is 9.1 Pa·s, which has good fluidity.
[0075] Example 3
[0076] This embodiment provides a method for preparing a silicon-based ceramic core sample, comprising the following steps:
[0077] 1. Parameter determination: Select the slice thickness as 100 μm, the slurry of Example 1 (light absorber content is 0.05), the exposure parameters are 5 s, 32 mW / cm 2 .
[0078] 2. Photocuring printing: inject the slurry of Example 1 into the printing material slot of the ceramic 3D printer, perform photocuring printing, and obtain a green body;
[0079] 3. Degreasing and sintering: Degreasing and sintering the green body, after sintering to a dense state, a high-precision sample is obtained, such as Figure 5 shown.
[0080] After testing, the error of the molded sample is ≤1.5%, the room temperature bending strength is ≥15MPa, the high temperature strength at 1500℃ is ≥20MPa, the porosity is ≥24.1%, and the sintering shrinkage is <2.5%.
[0081] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A light-cured silicon-based ceramic core slurry for investment casting, characterized in that: The silicon-based ceramic core slurry comprises the following components based on 100 parts by total weight: 70 to 85 parts by weight of ceramic powder, 10 to 25 parts by weight of photosensitive resin, 2 to 5 parts by weight of photoinitiator, 1 to 5 parts by weight of dispersant, 0.2 to 1.2 parts by weight of anti-settling agent and 0.01 to 0.2 parts by weight of light absorber; The ceramic powder is composed of fused quartz powder, alumina ceramic powder and zirconium silicate ceramic powder in a weight ratio of 50-90:5-15:2-10; The particle size of the fused quartz powder is 2-30 μm, and the purity is ≥95wt%; the particle size of the alumina ceramic powder is 20-40 μm, and the purity is ≥95wt%; the particle size of the zirconium silicate ceramic powder is 20-50 μm, and the purity is ≥95wt%.
2. The light-cured silicon-based ceramic core slurry for investment casting according to claim 1, characterized in that: The light absorber is a mixed azo compound.
3. The light-cured silicon-based ceramic core slurry for investment casting according to claim 1, characterized in that: The photosensitive resin is a mixture of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate and bisphenol A epoxy acrylate.
4. The light-cured silicon-based ceramic core slurry for investment casting according to claim 1, characterized in that: The photoinitiator is a mixture of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate; and / or, the dispersant is selected from at least three of a polyphosphate solution, a modified polyurethane solution, a phosphate ester, propylene glycol methyl ether acetate, butyl acetate or an alkylbenzene; and / or, the anti-settling agent is selected from at least three of a polyhydroxycarboxylic acid amide solution, a modified urea solution, xylene, isobutyl alcohol or N-methylpyrrolidone.
5. A method for preparing the light-cured silicon-based ceramic core slurry for investment casting according to any one of claims 1 to 4, characterized in that: The preparation method comprises: mixing various raw materials and ball milling them, followed by vacuum degassing.
6. Use of the light-cured silicon-based ceramic core slurry for investment casting according to any one of claims 1 to 4 in preparing complex silicon-based ceramic cores.
7. A method for preparing a silicon-based ceramic core, characterized in that: The preparation method comprises the steps of printing a blank by using a ceramic 3D printing device, and further degreasing and sintering the blank to obtain a silicon-based ceramic core finished product: The step of printing the blank comprises: setting the slice thickness to 10-40 microns, setting the printing parameters to 10-30s, 20-35mW / cm 2 , using a first silicon-based ceramic core slurry for printing; based on the total weight of the first silicon-based ceramic core slurry as 100 parts, it comprises the following components: 70-85 parts of ceramic powder, 10-25 parts of photosensitive resin, 2-5 parts of photoinitiator, 1-5 parts of dispersant, 0.2-1.2 parts of anti-settling agent and 0.15-0.2 parts of light absorber.
8. A method for preparing a silicon-based ceramic core, characterized in that: The preparation method comprises the steps of printing a blank by using a ceramic 3D printing device, and further degreasing and sintering the blank to obtain a silicon-based ceramic core finished product: The step of printing the blank comprises: setting the slice thickness to 40-80 microns, setting the printing parameters to 5-25s, 25-35mW / cm 2 , using a second silicon-based ceramic core slurry for printing; based on the total weight of the second silicon-based ceramic core slurry as 100 parts, it comprises the following components: 70 to 85 parts of ceramic powder, 10 to 25 parts of photosensitive resin, 2 to 5 parts of photoinitiator, 1 to 5 parts of dispersant, 0.2 to 1.2 parts of anti-settling agent and 0.1 to 0.15 parts of light absorber.
9. A method for preparing a silicon-based ceramic core, characterized in that: The preparation method comprises the steps of printing a blank by using a ceramic 3D printing device, and further degreasing and sintering the blank to obtain a silicon-based ceramic core finished product: The step of printing the blank comprises: setting the slice thickness to 80-120 microns, setting the printing parameters to 5-20s, 25-35mW / cm 2 , using a third silicon-based ceramic core slurry for printing; based on the total weight of the third silicon-based ceramic core slurry as 100 parts, it comprises the following components: 70 to 85 parts of ceramic powder, 10 to 25 parts of photosensitive resin, 2 to 5 parts of photoinitiator, 1 to 5 parts of dispersant, 0.2 to 1.2 parts of anti-settling agent and 0.05 to 0.1 parts of light absorber.
10. A method for preparing a silicon-based ceramic core, characterized in that: The preparation method comprises the steps of printing a blank by using a ceramic 3D printing device, and further degreasing and sintering the blank to obtain a silicon-based ceramic core finished product: The step of printing the blank comprises: setting the slice thickness to 120-200 microns, setting the printing parameters to 5-15s, 15-35mW / cm 2 , using a fourth silicon-based ceramic core slurry for printing; based on 100 parts by total weight of the fourth silicon-based ceramic core slurry, it comprises the following components: 70 to 85 parts of ceramic powder, 10 to 25 parts of photosensitive resin, 2 to 5 parts of photoinitiator, 1 to 5 parts of dispersant, 0.2 to 1.2 parts of anti-settling agent and 0.01 to 0.05 parts of light absorber.
Citation Information
Patent Citations
Ceramic slurry as well as preparation method and application thereof
CN112745107A
Silicon dioxide ceramic core for manufacturing turbofan engine and preparation method of silicon dioxide ceramic core
CN116675523A
Photocuring 3D printing ceramic core slurry and preparation method thereof
CN118359426A
High-performance silicon-based ceramic core capable of realizing balance of solid content and viscosity and preparation method of high-performance silicon-based ceramic core
CN118791291A
Foundry mould compsn - contg binder, refractory, surfactant and a phosphoric acid deriv
DE2616709A1